HEALTH TAKAFUL PLAN FOR PETS - Mohammad Firdaus Mohammad Hatta; Andi Nur Elisya Syahira Bahri; Siti Maisarah Ahmad Kamal; Siti Zaleha Sahak (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
For some pet owners, it might be difficult to afford for veterinarian care. One solution that helps lessen this burden is the availability of pet health Takaful. This study aims to measure people’s decision-making to buy their pet health Takaful. It is important due to the increase in people’s income which has triggered the birth of a community of pet lovers in Malaysia. To determine whether having PetCare Takaful affected public spend at the vet and how often they visited, the study conducted a qualitative approach through interview data collection to determine the public response to PetCare Takaful contributions. This study was conducted to provide empirical evidence that the decision-making of the animal lover community is affecting the contribution rate of PetCare Takaful that has been offered. Thus, this study strongly supports the development of Takaful companies in Malaysia, which can provide pet protection to stay healthy and well looked after. The amount spent at the veterinarian was found to be significantly and favorably impacted by PetCare Takaful. It was discovered that the informants preferred pet health Takaful relating to their pet medical expenses, following by the coverage for accidental death of the pet and the pet travel expenses.